PERKEMBANGAN PUISI ARAB MODERN - Taufiq A. Dardiri (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This article aims to study the development of Arabic poetry from its early phase to its modern one. Having used a historical-diachronic study of form and content of Arabic poetry, this article concludes that Arabic poetry, as the oldest genre in the Arabic literary tradition, has hardly developed. Not until the 20th century, more commonly known in the history of Arabic literature as Asr al-Nahdah, that the awareness of the absence of creativity in Arabic poetry and external factors due to the interaction of Arab with the West have given birth the seeds of modern Arabic poetry. At least, there are five schools of modern Arabic poetry, namely: Neo Classical (al-Muhāfizun) with such its central figures as Mahmud Sami and Ahmad al-Barudi Syauqy; Western Romanticism, which was pioneered by Khalil Mutran; Madrasah Dīwān, which was propagandized by Abd al-Rahman Shukri, Abbas Mahmud al-'Aqad, and Ibrahim Abd al-Qadir al-Mazini; Madrasah Apollo, which was carried by Ahmad Zaki Abu Syadi; and Madrasah al-Muhajir, which is pioneered by Jibran Khalil Jibran. Each has contributed their part in Arabic poetry formally as well as contentially. Those schools have became a tradition of modern Arabic poetry. The emergence of modern Arabic poetic tradition has been accompanied by three general pattern- the influence of literary patterns of the more advanced cultures, the escapism, and the search for identity.